Exercise-induced diaphragm fatigue in an elite adaptive rower with spinal cord injury - Romer, L. M.; Tiller, N. B.; Aggar, T. R.; West, C. R. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Exercise requiring heavy use of the arms forces the respiratory muscles to generate pulmonary airflow while providing postural stability to the thorax. The dual role for respiratory muscles during upper-body exercise likely impacts on respiratory mechanics and may induce fatigue of the associated musculature. Although diaphragm fatigue has been shown to occur in response to predominately lower-body exercise, it is not yet known whether this phenomenon occurs with upper-body exercise. Aims: To characterise mechanical ventilatory responses and exercise-induced diaphragm fatigue in an elite arms-only rower with spinal cord injury. Methods: A Paralympic, World and European Champion oarsman (category: 1×AS, age: 28 y, stature: 1.89 m, mass: 90.4 kg) with motor-complete spinal cord injury (T12) performed a 1000 m time-trial on an adapted Concept II rowing ergometer. Measurements included pulmonary function (spirometry, plethysmography, lung diffusion), ventilation and pulmonary gas exchange, central respiratory drive via diaphragm EMG (multi-pair oesophageal electrode catheter) and pressure-derived indices of respiratory mechanics. Diaphragm fatigue was assessed by measuring the twitch transdiaphragmatic pressure (Pdi,tw) response to anterolateral magnetic stimulation of the phrenic nerves before and up to 30 min after exercise. Results: Baseline pulmonary function exceeded the upper-limit-of-normal (FEV1: 5.5 L [114% predicted], VC: 7.6 L [130%], TLC: 10.1 L [126%], MVV: 262 L/min [141%]; DL,CO: 17.2 mmol/min/kPa [131%]). The 1000 m time-trial was completed in 3.9 min (248 ± 25 W) and induced peak values for minute ventilation and O2 uptake of 154 and 3.57 L/min, respectively. The breath-to-stroke ratio was 1:1 during the first 400 m and 2:1 thereafter (tidal volume: 2.67 ± 0.06 vs. 1.63 ± 0.82 L). Diaphragm EMG rootmean-square amplitude during inspiration was higher in the second half of the time-trial, yet inspiratory transdiaphragmatic pressure and tidal volume were lower. Relative to baseline, potentiated Pdi,tw was reduced by 33% at 15 min after exercise (40 vs. 59 cmH2O) and by 16% at 30 min (50 vs. 59 cmH2O). Conclusions: The results of this case-study indicate that exercise-induced diaphragm fatigue can occur in response to high-intensity upper-body exercise. The uncoupling of central respiratory drive and thoracic volume displacement suggests that diaphragm fatigue may be attributable, at least in part, to factors other than ventilation (e.g., postural drive).